Evaluation of the short form of “Experience in close relationships” (revised, German version “ECR-RD12”) - a tool to measure adult attachment in primary care - Brenk-Franz, Katja; Freund, Tobias; Schauenburg, Henning (PLOS ONE, 2018)
Attachment theory helps us to understand patients´ health behavior. Attachment styles might explain patient differences in coping behavior, self-treatment, or patient-provider relationships. In primary care time constrains are relevant. A short instrument may facilitate screening and assessment in daily medical practice. The aim of this study was to evaluate a 12-item short version of the Experience in Close Relationships-revised (ECR-R-D) to be used in primary care settings. We included 249 patients from ten general practices in central Germany into a cross-sectional study. Exploratory factor analysis was performed to evaluate the factor structure of the ECR-items. Cronbach’s alpha was used to assess internal consistency. The results related to the short form of the ECR are in line with those of the German full-length version of the measure (ECR-RD 36). Internal consistencies were in an adequate range. The ECR short form can be recommended as a screening measure of attachment styles in primary care.